Die Frau muss Vollmacht haben auf ihrem Haupt (1 Korinther 11,10). Zur Geschichte und Gegenwart feministischer Paulusauslegungen. (lectio difficilior, 2002)
Focusing on the exegesis of 1 Corinthians 11,2-16 and Galatians 3, 28, the essay traces the history of feminist exegesis of the Epistles of Paul. It will become evident that contemporary exegesis of Paul participates in the discussion of feminist theory and history in different ways. With the help of textual examples it will be shown how in an increasing plurality of approaches feminist research perceives the diversity of women who throughout history until today have interpreted and discussed Pauline theology.